Fulminant Septic Shock From Melioidosis And Leptospirosis Co-infections - Kai Yang Lim; Wan Fadzlina Wan Muhd Shukeri; Mohd Zulfakar Mazlan; Muhamad Rafiqi Hehsan; Huda Zainal Abidin (APICARE publication, 2024)
Indexed by WOS